Induced mutation of in vitro aquatic plant, Cryptocoryne xwillisii reitz by using gamma irradiation and IRAP analyses to distinguish the sports (clonal mutation) / Norhanizan Sahidin - Norhanizan, Sahidin (2012)
One part of ornamental fish industry is the aquatic plants. Ornamental fish industry is identifying as one of National Key Economic Area (NKEA) for Malaysia, under business opportunity. Cryptocoryne xwillisii Engler ex Baum is one of the highly demanded aquatic plants in international market. Unfortunately, the plants take months to grow, seldom flowering and no viable seeds. The studies were done to mass-produce the plants by tissue culture and to develop new variety by mutation. Tissue culture of water trumpet, Cryptocoryne xwillisii Engler ex Baum, was developed using Murashige and Skoog 1962 (MS) medium, which contained two different plant growth regulators, namely 6-benzyladenine purine (BAP) and α-naphthalene acetic acid (NAA). Seven different concentrations of BAP (0, 0.5, 1.0, 5.0, 10.0, 20.0 and 40.0 μM) and NAA (0, 0.5, 1.0, 5.0, 10.0, 20.0 and 40.0 μM) were investigated using a twofactor factorial design with 10 replicates. Results of the experiments were collected and analysed after 40 days of culture. The results showed that the effects of plant growth regulators on increasing the number of shoots were highly significant (p<0.01). The MS medium containing 1.0 μM BAP alone was the optimum concentration producing 6.8 ± 1.75 shoots per explant. This was the minimum formula concentration of BAP used that produced the highest number of shoots. Results showed that there were twelve hormone combinations giving high mean values of between 4 to 6 shoots per explant. All of the explants cultured in these media produced shoot (100 %). Although all the explants gave a positive response in terms of regeneration, they however differed in the number and size of shoots produced. Analysis of the data using ANOVA indicated that the number of shoots produced was significantly influenced by both BAP and NAA concentrations simultaneously. This was suggested by the significance of the interactions between BAP and NAA which showed that BAP concentrations affected the number of shoots differently for each concentrations of NAA tested and vice versa. Two new varieties of C. xwillisii have been developed through mutagenesis in this work. Shoot tips explants of C. xwillisii were subjected to a range of 60Co gamma ray irradiation of 0, 100, 200, 300, 400, 500, 600, 700 and 800 Gray. Results from experiments showed that the LD50 for the tissue culture plants of C. xwillisii was at 32 Gy dose. And was therefore, less than 32 Gray was used as the appropriate dosage for induced mutations of the plants. About two thousand of the shoot tips explants were irradiated using the 25 Gy and variants from the M1, M2, M3 and M4 generations were screened for morphological differences. The variants shoots were subcultured repeatedly until the 4th generation (M4) to ensure stability of mutants. Although initially many regenerants with different morphological traits were produced, only two mutants were shown to remain stable. The mutants obtained were dwarf plants (D1) and plants of taller stature with pigmented leaves (G1) than the controls. This was verified from the significant value of the F test in the ANOVA where P<0.05. The Inter-Retrotransposon Amplified Polymorphism (IRAP) markers distinguished the D1 and G1 genomes from normal C. xwillisii genomes. The analysis revealed two specific bands 325 bp and 420 bp using Nikita primer for the D1 mutant and 240 bp and 300 bp using combination of 3’LTR primer and LTR 6149 primer for the G1 mutant.